Facebook in an English Guided Self Learning Class - Melania Wiannastiti (Bina Nusantara University, 2013)
The use of technology especially the Internet in language teaching and learning has become more popular nowadays since it is more interesting and effective. Nowadays, since almost every person has at least a gadget connected to the Internet, the teaching learning is possible to be carried out outside the classroom in the way of autonomous learning. Language learners are likely to look to computers and the Internet for resources of learning. By applying the Internet as the type of learning, students are exposed to optimize the use their gadget connected to the Internet. This type of learning was also applied for Binus pre-university students learning English Smart Program in GSLC (Guided Self Learning Class). Based on the background, this paper aims to explain what GSLC is and describe how Facebook as the Internet social media can be used for supporting GSLC. There are many advantages the students and the lecturer get from using this media in GSLC. From result of the questionnaire, FB is affective to support them in learning. In conclusion, Facebook can be used to support the GSLC activities.